2018
DOI: 10.1007/s10488-018-0848-z
|View full text |Cite
|
Sign up to set email alerts
|

Interventions at the Transition from Prison to the Community for Prisoners with Mental Illness: A Systematic Review

Abstract: Prisoners have high rates of mental illness and the transition from prison to the community is a problematic time for the provision of mental health services and a range of negative outcomes have been identified in this period. A systematic review was conducted to identify interventions for prisoners with diagnosed mental health conditions that targeted this transition period. Fourteen papers from 13 research studies were included. The interventions identified in this review were targeted at different stages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
87
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 36 publications
1
87
0
2
Order By: Relevance
“…This period requires adjustment to new freedoms and pressures as well as the establishment of new routines and possibly new support mechanisms. In their systematic review, Hopkin et al, (2018) noted several key factors as important for successful transitions.…”
mentioning
confidence: 99%
“…This period requires adjustment to new freedoms and pressures as well as the establishment of new routines and possibly new support mechanisms. In their systematic review, Hopkin et al, (2018) noted several key factors as important for successful transitions.…”
mentioning
confidence: 99%
“…Considering parallels in the difficulties experienced by ex-service personnel accessing civilian health and social care services with other health and social care transitions (eg, poor continuity of care and health and social care outcomes experienced by those leaving prison with mental health problems),24 it is suggested that the benefits experienced by veterans may be transferable. Future development and research should consider translation for other populations.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike Assertive Community Treatment (ACT) and Critical Time Intervention (CTI), the programme did not provide case management in the post-release period. Although this may be viewed as a limitation of the PReP Programme, previous studies ( 22 , 29 , 40 ) and a recent systematic review ( 24 ), have highlighted the importance of pre-release planning in any intervention to aid the transition for mentally disordered offenders. We acknowledge that the less intense follow up provided by our programme results in difficulty determining the quality of engagement with mental health and other supports in the post-release period.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their complex healthcare needs, programmes for prison populations are conspicuous by their absence in these clinical strategies. It has been suggested that enhanced coordination between medical and mental health teams, and early identification of needs prior to release, can promote involvement of community based supports and assist in achieving continuity of care ( 22 24 ). These recommendations are echoed in Human Rights legislation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation